Vanadiniferous micaceous concretions in the Patquia Formation (Permian), Sierra de Maz, Province of La Rioja - Caselli, A.T. (1997)
These concretions form discrete spherical bodies 2 to 20 cm in sizes, within medium grained massive sandstone (arkosic arenite). Three concentric zones are recognized: a) dark green to black core composed of quartz and feldespar cemented by illite and roscoellite, b) an intermediate pale red zone of hematite-coated quartz, and c) a white, iron-leached outer zone. Edax and ICP analyses reveal high concentrations of vanadium mainly in zones a) and b) (60340 and 2582 ppm respectivily), uranium (237 and 163 ppm), rubidium (252ppm) and copper (178ppm). The concretions are interpreted as formed under eodiagenetic conditions before the development of haematite cement which gave the red colour to the host rock.